2013
DOI: 10.4172/1948-593x.1000098
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Cymbopogon Citratus Against Diabetes: Validation by In vivo Experiments and Computational Studies

Abstract: This study evaluates the antidiabetic activities of essential oil obtained by steam distillation of the leaf sheath of Cymbopogon citratus (CCEO) in poloxamer-407 induced type 2 diabetic (T2D) Wistar rats. The sample was then analyzed by gas chromatography-mass spectroscopy (GCMS) identifying 23 compounds representing 96.9% of the oil. The major compounds of essential oil were geranial (42.4%), neral (29.8%), myrcene (8.9%) and geraniol (8.5%). When compared to diabetic control rats, the CCEO treated diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
0
9
1
1
Order By: Relevance
“…In some previous studies, treatment of lemongrass ethanol and aqueous extracts to non-diabetic animals reduced blood glucose by 21.3% and 19.8%, respectively [11,14]. Similarly, administration of essential oil or aqueous extract reduced blood glucose by about 47.3% and 42.4% in hyperlipidemic and diabetic animals, respectively [15,16]. However, in our present study, consumption of…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In some previous studies, treatment of lemongrass ethanol and aqueous extracts to non-diabetic animals reduced blood glucose by 21.3% and 19.8%, respectively [11,14]. Similarly, administration of essential oil or aqueous extract reduced blood glucose by about 47.3% and 42.4% in hyperlipidemic and diabetic animals, respectively [15,16]. However, in our present study, consumption of…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, boiling has been the widely method used for the preparation of lemongrass as beverage for nourishment and for the traditional treatment of diabetes across most parts of the world. Interestingly, Bharti et al [16] have reported the hypoglycemic, hypolipidemic and antioxidant potential of lemongrass essential oils in hyperlipidemic rats. The main constrains to this study were lack of using T2D animal model and essential oils may not contain some polar component of lemongrass such as the flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of sesquiterpene hydrocarbons such as Germacrene B and Germacrene D in the essential oil could be the reason for cytotoxic activity [20]. Chemical composition of Guazuma ulmifolia essential oil could be suggested as potential source of natural antioxidant and antimicrobial for food industry [21].…”
Section: Treatment On Various Human Diseasesmentioning
confidence: 99%
“…In addition, myrcene, geraniol, borneol, citronellol, limonene, a-terpineol, elemicin, nerol, catechol, luteolin, apigenin, quercetin, kaempferol, glycosides, chlorogenic acid, caffeic acid, geranyl acetate as well as methylheptenone, isovaleric aldehyde, fumesol, L-linalool, furfurol, isopulegol, ndecyclic aldehyde, p-coumaric acid, terpinene are also evident in trace amount in several studies [12][13][14]. There are also reports on the presence of isoscoparin, swertiajaponin, orientin and other phytochemicals in lemongrass [15,16]. The amount of major constituents of lemongrass EO found in studies which shows a greater presence of trans-citral (geranial) and ciscitral (neral) along with more reduced amounts of nerol, geraniol, citronellol, terpinolene, geranyl acetate, myrcene, a-terpineol and other components.…”
Section: Chemical Composition Of Lemon Grassmentioning
confidence: 99%